1996
DOI: 10.1007/s004240050160
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-optical measurements of chloride movements in cells using the membrane-permeable dye diH-MEQ

Abstract: Fluorescence-optical measurements of the intracellular chloride concentration facilitate identification of chloride movements across the cell membrane of living cells. The two main dyes used for this purpose are 6-methoxy-N-(3-sulfopropyl)quinolinium (SPQ) and 6-methoxy-quinolyl acetoethyl ester (MQAE). The use of both substances is impaired by their poor membrane permeability and therefore limited loading of the cells to be studied. Here we report the use of 6-methoxy-N-ethylquinolinium iodide (MEQ), a chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…Measurements of cellular anion entry were then performed by SCN Ϫ -quenching of the halide-sensitive fluorescent dye MEQ. In an earlier study it was demonstrated that the MEQ quench measured in NIH 3T3 fibroblasts is strongly enhanced in cells swollen by hypotonicity and that antisense oligodeoxynucleotides specifically knocking down ICln considerably impede both the MEQ quench and RVDC in NIH 3T3 fibroblasts (36). As shown in Fig.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Measurements of cellular anion entry were then performed by SCN Ϫ -quenching of the halide-sensitive fluorescent dye MEQ. In an earlier study it was demonstrated that the MEQ quench measured in NIH 3T3 fibroblasts is strongly enhanced in cells swollen by hypotonicity and that antisense oligodeoxynucleotides specifically knocking down ICln considerably impede both the MEQ quench and RVDC in NIH 3T3 fibroblasts (36). As shown in Fig.…”
Section: Discussionmentioning
confidence: 75%
“…diH-MEQ (Molecular Probes) was prepared as described earlier (36). Cells were loaded for 10 min with 5 M diH-MEQ, washed, and superfused with either a control solution (in mM: sodium gluconate 131, potassium gluconate 5.4, MgSO 4 0.8, calcium gluconate 1.2, NaH 2 PO 4 1, glucose 5.5, Tris 5, pH 7.4), or with a hypotonic solution (sodium gluconate reduced to 81 mM).…”
Section: Meq Fluorescence Quenchingmentioning
confidence: 99%
See 1 more Smart Citation
“…MEQ was loaded into cells after reducing it to DiH-MEQ by adding 30 M sodium borohydride (100 l) to MEQ (5 mg) under a continuous stream of nitrogen gas (Woll et al 1996). DiHMEQ enters cells during the incubation period (15 min), where it is oxidized and retained in the form of MEQ.…”
Section: Imaging Experimentsmentioning
confidence: 99%
“…MEQ was loaded into cells after reducing it to DiH-MEQ by adding 30 μM sodium borohydride (100 μl) to MEQ (5 mg) under a continuous stream of nitrogen gas (Wöll et al, 1996). DiH-MEQ that enters cells during the incubation period (15 min) is oxidized and retained in the form of MEQ.…”
Section: Imaging Experimentsmentioning
confidence: 99%